Influence of histology and biomarkers on first-line treatment of advanced non-small cell lung cancer in routine care setting: Baseline results of an observational study (FRAME) - Schnabel, Philipp Albert (Lung cancer, 2012)
FRAME is a prospective observational study of first-line treatments for advanced non-small cell lung cancer (NSCLC). This interim analysis examines the influence of histology and biomarkers on therapeutic decisions. Baseline characteristic, treatment, and diagnostic procedure data were collected on European patients with stage IIIB/IV NSCLC who were treated with any first-line platinum-based doublet, with or without targeted agents, in routine clinical practice. A total of 1567 patients were observed in 11 countries between April 2009 and February 2011. Patients were mostly non-Asian (96.4%), male (71.5%), smokers (84.4%) with stage IV NSCLC (76.6%) and a performance status of 0-1 (82.2%). Median age was 64 years (range, 33-87). First-line treatments were platinum-based combinations with pemetrexed (36.3%), gemcitabine (23.0%), vinorelbine (19.2%), taxanes (18.9%), or other (2.6%), with concurrent targeted agents in 8.4% of patients (mainly bevacizumab, 7.3%). Diagnosis was based on histology in 70.6%, cytology in 20.3%, and both in 9.1% of patients. The final diagnosis was nonsquamous in 72.2% (including ‘not otherwise specified [NOS]’ in 11.0%), squamous in 24.4%, and other in 3.4% of patients, with the most common reasons for NOS diagnosis being ‘subtyping not technically possible’ (42.9%) and ‘not important for treatment decision’ (40.5%). Only 1.1% (6 patients) in the pemetrexed cohort and 0.9% (1 patient) of patients who received bevacizumab had squamous cell carcinoma. At least one immunohistochemical (IHC) marker was used in 53.5% of patients (thyroid transcription factor-1 [TTF-1]: 47.5%, cytokeratin 7 [CK7]: 38.6%, cytokeratin 5/6 [CK5/6]: 17.9%, p63: 8.8%, cluster of differentiation 56 [CD56]: 4.2%, cytokeratin 14 [CK14]: 1.9%, and other: 24.2%). Testing for additional biomarkers was less common, with the most common being for epidermal growth factor receptor (EGFR) mutation status (26.0%). Physician-reported key factors influencing treatment choice were ‘histopathological/cytological diagnosis’ (77.4%), ‘performance status’ (63.2%), and ‘age’ (52.8%). Similar factors were identified using logistic regression models. Frequent histological testing was observed, likely resulting in few NOS diagnoses. In addition, IHC and predictive biomarkers were routinely assessed. Histology, performance status, and age were key factors influencing first-line treatment choice in the routine care of patients with advanced NSCLC. Clinical Trials. gov registry identifier number: NCT01067794.